Answer:
Polygon A is reflected across x- axis followed by the reflection across y-axis.
Explanation:
A polygon A has been transformed by a rigid transformation to form an image polygon B.
Let one of the vertex of polygon A is (-2, 1).
When polygon is reflected across the x - axis,
Image point will be,
A(x, y) → A'(x, -y)
By this rule,
A(-2, 1) → A'(-2, -1)
Now the image point is further reflected across the y-axis,
Rule for the reflection across y-axis is,
A'(x, y) → B'(-x, y)
By this rule, image of A' will be,
(-2, -1) → (2, -1)
Therefore, Polygon A is reflected across x- axis followed by the reflection across y-axis.